2020
DOI: 10.3390/ijms21176290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-6 Signaling Pathway Inhibition on Weight and BMI: A Systematic Review and Meta-Analysis

Abstract: Inhibitors of the IL-6 signaling pathway, such as tocilizumab, are frequently administered for the treatment of immune diseases, e.g., rheumatoid arthritis and multicentric Castleman’s disease. The aim of this systematic review and meta-analysis was to ascertain the effects of IL-6 pathway inhibitors on weight and body mass index (BMI). Using PRISMA guidelines, we systematically reviewed relevant articles from three databases (PubMed, OVID, EMBASE). A random effects model was used to estimate standardized mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 67 publications
0
27
0
2
Order By: Relevance
“…Altered concentrations of inflammatory markers may not only be of scientific interest as biomarkers or pivotal messenger molecules involved in the pathophysiology of AN. They may also represent future drug targets, because inhibitors of certain cytokine pathways are available and approved for the treatment of autoimmune disorders, and they have also been shown to influence weight in meta-analytic research [ 34 , 35 ]. Additional treatments such as non-steroidal anti-inflammatory drugs, omega-3 fatty acids, statins and minocyclines have shown anti-inflammatory effects in major depressive disorder [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altered concentrations of inflammatory markers may not only be of scientific interest as biomarkers or pivotal messenger molecules involved in the pathophysiology of AN. They may also represent future drug targets, because inhibitors of certain cytokine pathways are available and approved for the treatment of autoimmune disorders, and they have also been shown to influence weight in meta-analytic research [ 34 , 35 ]. Additional treatments such as non-steroidal anti-inflammatory drugs, omega-3 fatty acids, statins and minocyclines have shown anti-inflammatory effects in major depressive disorder [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that whilst the LCV data supported strong partial genetic causality of CRP on AN, the MR evidence was less statistically significant, with some evidence in the MVMR that IL-6 signalling may exert a protective effect on AN conditioned-on CRP. Inhibition of the IL-6 pathway has been associated with weight gain which may be protective for AN (81). Furthermore, CRP likely is intertwined with other metabolic factors, including insulin signalling, which our group has previously shown through MR is also putatively protective for AN (48).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that elevated proinflammatory cytokines, and IL-6 in particular, may serve as state markers for AN. Moreover, a recent meta-analysis revealed that selective inhibition of the IL-6 signaling pathway is associated with an increase in weight gain [ 62 ]. This suggests that the IL-6 signaling pathway is involved in the regulation of body weight and could thus be targeted by available pharmacological IL-6 inhibitors to facilitate weight gain in AN patients.…”
Section: Anorexia Nervosa and Peripheral Inflammationmentioning
confidence: 99%